El género bromus en los andes centrales de suramérica (1986)
A preliminary taxonomic revision of the brorne-grass species is found in Bolivia and Perú, with keys, drawings (mostly of type specimens), synonymies, descriptions and extensive specimen citations, 5 species are recognized: Bromus catharticus, B. lanatus, B. pitensis, B. trinii and  B. villosissimus. It is established stat. noy. for B. striatus. The grow in the higher  mountain regions above 2000 m and up to the snow line. B. catharticus is reported from the coast and the var. striatus is found up to 600 m.